The Effect of Performance Appraisal System on Organizational Commitment: Case Study Gaza Electricity Distribution Corporation - Wasim Swidan; Ali Al-Tahitah; Kalsom Ali (USIM Press, 2024)
Journal of Islamic Social Sciences and Humanities (Al-'Abqari) Volume 29 No.1 Page(108-134)